DESIGNING A CONTROL SYSTEM FOR MECHANISMS WITH VARIABLE IMBALANCE - ПАВЛЕНКО, В. М.; КУРЛЯК, П. О.; ВОЛЯНИК, О. Ю. (Technologies and Engineering, 2024)
Purpose. Conducting analytical and experimental research, developing a control system for mechanisms with a variable imbalance. Investigation of operating modes, verification of the operation algorithm and determination of steady states of the unbalanced mechatronic system. Determination of dependencies that describe the nature of the load on the working bodies. Methodology. Methods of mathematical modelling of mechatronic systems by constructing Bond Graph, algorithmic design, experimental study with data collection were used. Results. An analytical review of the nature of formation and methods of decreasing imbalance in unstable mechatronic systems is carried out, and a system for automatic control of rotor balancing using digital monitors in centrifuges with variable imbalance is developed and proposed. The control system includes a microcontroller, a Hall sensor, and a BondGraph model for modelling the operation of an induction motor. An algorithm was developed for the control program, which, according to the set parameters, checks the nominal and critical current values in the centrifuge drive. The current value is recorded and fluctuations are monitored. If the current increases, the system reduces the speed by 10% to reduce the amplitude of oscillations in transient rotation modes, while continuing to monitor the permissible current limit and motor load. Scientific novelty. The article analyses aspects of emergence and studies regulation of unbalanced systems. A structural diagram of the control system for rotary mechanisms with the use of digital monitoring is proposed. The system control algorithm is developed. The study of unstable states using BondGraph computer modelling methods was carried out. Practical significance. As a result of the analytical study, the phenomenon of imbalance in mechatronic systems was considered. An experimental model for controlling unbalance in rotary centrifugal mechanisms was designed and implemented. The results and conclusions obtained can be used in the design of centrifugal machines in various industries.